Identification of Underpricing Factors Initial Public Offering (IPO) Manufacturing Sector on The Indonesia Stock Exchange - Irawan, Irawan; Nasution, Ilham Ramadhan (Management Research and Behavior Journal, 2023)
This study aims to prove and analyze the effect of Return On Assets (ROA), Inflation Rate, Earning Per Share (EPS) and Debt to Asset Ratio (DAR) on Underpricing of shares in manufacturing companies during the initial public offering (IPO) on the Indonesian Stock Exchange in 2017-2021 years. This research design is quantitative with an associative approach. The population in this study were all manufacturing companies that experienced stock underpricing in 2017 – 2021, while the samples used in this study were 53 manufacturing companies that met certain criteria in the study period. The sampling technique used purposive sampling method. The data analysis used is multiple linear regression analysis. The results of this study indicate that Earning Per Share (EPS) has a significant negative effect on underpricing and the Inflation Rate has a significant positive effect on underpricing, while Return On Assets (ROA) and Debt to Asset Ratio (DAR) have no effect on underpricing. The high or low value of Return on Assets and debt to asset ratio does not significantly affect stock underpricing during the initial public offering. The value of earnings per share and inflation greatly affects the underpricing of shares in manufacturing companies during the initial public offering